Guinea-Bissau : 2006 Article IV Consultation Review of Developments Under the 2005 Staff-Monitored Program and New Staff-Monitored Program for 2006 Staff Report; Public Information Notice on the Executive Board Discussion; and Statement by the Executive Director for Guinea-Bissau. (IMF Staff Country Reports; Country Report ;, 2006)
Despite abundant natural resources and arable land, Guinea-Bissau is ranked at the lowest end of the UN human development index, mainly because of the civil war of 1998-99 and the ensuing prolonged political instability and serious governance deficiencies thereafter. Since mid-2004, Guinea-Bissau has made a major effort to address the political and economic problems of recent years. The fiscal balance improved, but cash flow problems persisted throughout 2005. Higher imports and strengthened tax and customs administration helped buoy tax revenue.